P450 Vaccination strategies in Inflammatory Bowel Disease patients: perspective of physicians and patients. (27th May 2021) - Ferreiro Iglesias, R; Hernández Camba, A; Saldaña, R; Rodríguez-Lago, I; Zabana, Y; Barreiro-de Acosta, M
Abstract: Background: Despite the existence of specific recommendations, patients with Inflammatory Bowel Disease (IBD) have shown low immunization rates. The aim of this study was to evaluate the management of vaccines in clinical practice in IBD from the perspective of physicians and patients. Methods: An online anonymous survey was sent to 8000 patients from a national patient association (ACCU-Spain) and 1000 members of the Spanish IBD Working Group (GETECCU). Three invitations were sent between October-December 2020. Forty questions were jointly designed by ACCU and GETECCU in two different surveys for physicians and patients. Descriptive analyses were performed, comparing physician's and patient's responses by standard statistical analyses Results: 144 physicians and 1302 patients responded to the surveys (overall mean age of 43 years (SD 9.5). 65% of physicians managed more than 200 patients and 80% had >5 years of experience. Most physicians (99%) were concerned about vaccines in IBD patients in their clinical practice, and 63% of them considered vaccines very important. Only 3.5% of physicians recommended live vaccines for their IBD patients with immunosuppressive treatments. One third of physicians did not recommend HPV vaccine. In spite of 69% of physicians recommending influenza vaccine during pregnancy, only 7.2% of pregnant patients indicated that they had received advice on influenza vaccination on their pregnancy (p<0.001). Only 16.6% of physicians recommended live vaccines during the first year of life in children born to mothers exposed to biologics, and 4.4% did not recommend inactive vaccines. Moreover, patients treated with biologics considered that physicians were well trained in vaccines, compared to those treated with other drugs. Table 1 summarizes the perspective of physicians and patients. Conclusion: Deficiencies in knowledge regarding vaccination of IBD patients can be frequent. The perspective of physicians and patients is different, with physicians perceiving more recommendations related to vaccines than patients were recommended.